Students' Difficulties in Answering PISA-Like Problems in the Context of North Sumatra at SMP Xaverius 2 Palembang - Ruth Magdalena Suryaningsih; Hartono Hartono; Melly Ariska (Institute of Multidisciplinary Research and Community Service, 2023)
Abstract: At present students often have difficulty answering and solving questions, especially international standard questions in the form of PISA. The existence of a difficulty faced by students is a lack of interest in reading so that literacy in Indonesia is very low, especially on the results of the PISA test. The purpose of this study was to find out the difficulties experienced by students in answering PISA questions like the context of North Sumatra, the factors that influence difficulties in answering questions generally lie in the use of formulas, understanding or the ability to digest the language in the texts of PISA questions. This type of research is descriptive research that aims to identify and describe the difficulties experienced by students in answering PISA Like questions in the context of North Sumatra. The results of this study indicate that in answering PISA questions students experience difficulties in understanding the questions, changing and solving real problems in the form of science, namely physics, and interpreting physics solutions in real situations. The results show that difficulties in understanding questions and changing real problems into physics are more dominant than difficulties in PISA biology questions. Keywords: student difficulties, pisa, pisa like the context of north sumatra